2023
DOI: 10.1101/2023.07.04.547679
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-catalytic function of PRC2 in the control of small RNA dynamics during programmed genome elimination inParamecium

Abstract: To limit transposable element (TE) mobilization, most eukaryotes have evolved small RNAs to silence TE activity via homology-dependent mechanisms. Small RNAs, 20-30 nucleotides in length, bind to PIWI proteins and guide them to nascent transcripts by sequence complementarity, triggering the recruitment of histone methyltransferase enzymes on chromatin to repress the transcriptional activity of TEs and other repeats. In the ciliate Paramecium tetraurelia, 25-nt scnRNAs corresponding to TEs recruit Polycomb Repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 59 publications
3
6
1
Order By: Relevance
“…We extended the scnRNA analysis by sequencing total small RNAs in the 20- to 30-nt range from Gtsf1-depleted cells at several time points (from T=0 to T=35 hours after the onset of autogamy) (Figure S1; Figure S5). In Gtsf1-depleted cells, the 25-nt scnRNAs are produced from the whole MIC genome at the beginning of the sexual cycle (T=0 hours), as in control RNAi conditions, consistent with previous work (Miró-Pina et al, 2023) (Figure 6B-C). This can be clearly observed when examining the mapping of 25-nt scnRNAs across an individual genomic region (Figure 6B), where MAC sequences, as well as MIC sequences (IES and OES), are covered.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…We extended the scnRNA analysis by sequencing total small RNAs in the 20- to 30-nt range from Gtsf1-depleted cells at several time points (from T=0 to T=35 hours after the onset of autogamy) (Figure S1; Figure S5). In Gtsf1-depleted cells, the 25-nt scnRNAs are produced from the whole MIC genome at the beginning of the sexual cycle (T=0 hours), as in control RNAi conditions, consistent with previous work (Miró-Pina et al, 2023) (Figure 6B-C). This can be clearly observed when examining the mapping of 25-nt scnRNAs across an individual genomic region (Figure 6B), where MAC sequences, as well as MIC sequences (IES and OES), are covered.…”
Section: Resultssupporting
confidence: 90%
“…To immunoprecipitate Gtsf1, we prepared nuclear extracts from control Paramecium cells and cells expressing the functional fusion protein. As expected, immunofluorescence experiments confirmed that Gtsf1, like Ptiwi09 (Bouhouche et al, 2011; Miró-Pina et al, 2023), localizes in the maternal macronucleus during meiosis (Figure 2D). Immunoprecipitation (IP) of the FLAG tag in triplicates for control and Gtsf1 (Figure 2E, Figure S1) was followed by MS (Figure 2F and 2G).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations